Determination of the origin of oral squamous cell carcinoma by microarray analysis: Squamous epithelium or minor salivary gland?. Issue 10 (21st September 2018) - Kinouchi, Makoto; Izumi, Sayaka; Nakashiro, Koh‐ichi; Haruyama, Yasuo; Kobashi, Gen; Uchida, Daisuke; Hasegawa, Tomonori; Kawamata, Hitoshi
Abstract : More than 90% of oral cancers are histopathologically squamous cell carcinomas (SCCs). According to clinical behavior and histopathological features, we hypothesize that oral SCC can originate from either oral squamous epithelium or minor salivary glands. Here, we examined whether some oral SCCs originate from minor salivary glands, and investigated whether these tumors show particularly aggressive biological behavior. The mRNA expression profiles of samples obtained from six patients with oral floor SCC (five men, one woman; mean age, 62.7 years) were analyzed using a microarray containing 32, 878 probes. The six samples were divided into two groups by clustering of expression levels of 845 probes differentially expressed in normal oral squamous epithelium and normal salivary glands. The expression profile in four cases was similar to that of normal oral squamous epithelium, and in two cases was similar to that of normal salivary glands. Furthermore, we identified nine genes that reveal the origin of the oral SCC. Subsequently, we examined the expression levels of these nine marker genes by reverse transcriptase‐polymerase chain reaction to determine the origin of 66 oral SCCs. Twelve of the 66 oral SCCs were considered to originate from minor salivary glands, and these tumors showed high metastatic potential ( p = 0.044, Chi‐square test). Furthermore, SCC derived from minor salivary glands showed a poor event‐free survival rate ( p = 0.017, Kaplan–Meier analysis). In conclusion, determination of the origin of oral SCC is helpful in planning treatment for patients with oral SCC. Abstract : What's new? In spite of several past attempts, no distinct factors controlling the biological aggressiveness of oral squamous cell carcinoma (SCC) have been identified. Determining the origin of the cancer cells could help predict biological aggressiveness, however. Here, the authors provide evidence that oral SCC has two different origins, as mucosal or salivary SCC. Furthermore, they identify nine genes able to reveal the origin of oral SCC. Based on their expression levels, the authors determined that twelve of the 66 oral SCCs in their sample originated from minor salivary glands. Salivary SCC tumors showed high metastatic potential and poor event‐free survival rate.